Effect on thermal properties of nanocellulose fibre (NCF) reinforced biodegradable polyhydroxylalkanoates (PHA) composite - Nazaruddin, N. S.; Saidatul Shima, Jamari (Universiti Malaysia Pahang, 2021)
Currently, biodegradable materials like polyhydroxyalkanoates (PHA) and polylactic acid (PLA) are receiving huge attention from the both scientific and industrial sectors. However, since PHA has poor thermal properties, there is a shortfall in the exploration of PHA ability with filler. Therefore, this research aim is to investigate the thermal effect of nanocellulose fiber (NCF) fillers with PHA polymer. The first solution of PHA composite is prepared by dissolving 1g of PHA in 40mL of dichloromethane at 30°C for 10 minutes. The PHA-NCF composite solution is prepared by adding 1wt%, 2wt%, 3wt%, and 4wt% of NCF dissolved in 40 mL of dichloromethane into the PHA solution. The mixture solution is agitated at 45°C with a magnetic stirrer for 10 minutes. The mixture is poured into a petri dish. The prepared films were characterized by Differential Scanning Calorimeter (DSC), Fourier Transforms Infrared Spectroscopy, (FTIR), and Thermogravimetric Analysis (TGA). The FTIR analysis shows that all PHA/NCF composite samples contain similar functional groups when compared with the pure PHA. No significant changes on the thermal properties of the PHA composite was observed with the addition of NCF fillers. However, comparison within the PHA/NCF samples shows that the PHA with 2% of NCF has a higher melting temperature and requires the highest enthalpy of melting. Hence, the addition of 2% of NCF is selected to be the optimum amount of NCF filler addition to the PHA composite.